2006
DOI: 10.1080/13504850500393402
|View full text |Cite
|
Sign up to set email alerts
|

On the validity of conventional statistical tests given evidence of non-synchronous trading and non-linear dynamics in returns generating process

Abstract: Based on the recent developments in market microstructure and applications of nonlinear dynamics and chaos theory to financial time series, the subsequent article questions the validity of traditional methods used to test the efficient market hypothesis. In particular, it emphasizes the invalidity of unit roots tests since they are not predictability tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
0
15
0
2
Order By: Relevance
“…A recent article by Saadi et al (2006) has questioned the validity of those conventional statistical tests for testing EMH, and their criticisms applied to all earlier Chinese studies, since the efficiency of SHSE and SZSE was empirically examined using statistical tests that are designed to uncover linear correlations of price changes. Specifically, the statistical inferences of efficiency/inefficiency drawn from those conventional efficiency tests are on very shaky grounds.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…A recent article by Saadi et al (2006) has questioned the validity of those conventional statistical tests for testing EMH, and their criticisms applied to all earlier Chinese studies, since the efficiency of SHSE and SZSE was empirically examined using statistical tests that are designed to uncover linear correlations of price changes. Specifically, the statistical inferences of efficiency/inefficiency drawn from those conventional efficiency tests are on very shaky grounds.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent article, Saadi et al (2006) questioned the validity of these conventional statistical tests for testing EMH on three grounds. First, a number of studies have shown that institutional features such as thin trading may generate spurious linear dependence in returns data.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations